(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the significance of teaching sophistication to preschool-aged children, emphasizing how early development of cognitive, social, and emotional skills can foster lifelong learning and adaptability. The study delves into relevant literature, outlines effective methodologies, and presents findings that underscore the importance of integrating sophisticated learning frameworks at an early age. Recommendations for educators and parents are provided.